Winning engaged consumers: The rules of brand engagement and intention of co-creation in social commerce - Bazi S.; Hajli A.; Hajli N.; Shanmugam M.; Lin X. (Emerald Group Holdings Ltd., 2023)
Purpose: Under the sunlight of social commerce, few concepts have blossomed like value co-creation. But when blurred strategies are implemented, the opportunity to wilt a brand is high. To avoid the miscues and the controversies, an ascendant step is to engage consumers with social commerce sites. The purpose of this paper is to propose three antecedents to engage consumers with social commerce sites, namely, social support, social commerce value and social commerce information sharing, and the effect of brand engagement on the intention of brand co-creation. Design/methodology/approach: This study used survey data from 234 Iranians with experience using social commerce sites. Variance-based structural equation modeling using the partial least squares path modeling approach was adopted to analyze the structural model. Findings: The authors found that social support, social commerce value and social commerce information sharing positively foster brand engagement. The study also revealed that brand engagement is a significant predictor of brand co-creation intention. Originality/value: The study is the first study that considers and explains brand engagement from social support theory, social commerce value theory and social commerce information exchange. Also, the study shows how consumers can be an integral part of a brand. Unlike other studies which were done in industrialized countries, this study was employed in Iran. 2019, Emerald Publishing Limited.